Hypercalcemia related to cholangiocellular carcinoma - Onalan, Erhan (Wiley, 2019)
Patients with malignancies may develop hypercalcemia due to bone metastases or paraneoplastic reasons. Hepatocellular cancer should be considered in liver masses detected in chronic viral hepatitis B patients with delta agents. However, in our case, we detected cholangiocellular carcinoma in the etiology of hypercalcemia.
Keywords: cholangiocellular cancer; delta hepatitis; hypercalcemia; malignancie; paraneoplastic